2023
DOI: 10.1177/09544070231163428
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of real-world emissions of China III and China IV buses in a high-altitude city: A case study of Lhasa

Abstract: Limitations still remain among vehicle emissions standards and regulations about high-altitude areas at altitude over 2400 m. In view of high vehicle-use intensity for buses, on-road measurements were performed on four heavy-duty diesel vehicles by employing a portable emissions measurement system (PEMS) in Lhasa, with an average elevation of approximately 3650 m. The result indicated that under real-world driving conditions of Lhasa, compared with China III buses, China IV buses did not show excellent emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Cavan McCaffery, HanweiZhu, and other researchers [34] concluded that diesel vehicles typically exhibit higher brake NOx emissions compared to CNG vehicles, and diesel hybrids have higher emissions compared to CNG and LPG vehicles. Meng Lyu et al [35] compared China-III and China-IV heavy-duty diesel vehicles at an altitude of 3650 m. The experimental results showed that SCR can effectively affect NOx emissions and concluded that there is a strong correlation between the relative emission factors of O 2 and NOx and the average vehicle speed.…”
Section: Introductionmentioning
confidence: 99%
“…Cavan McCaffery, HanweiZhu, and other researchers [34] concluded that diesel vehicles typically exhibit higher brake NOx emissions compared to CNG vehicles, and diesel hybrids have higher emissions compared to CNG and LPG vehicles. Meng Lyu et al [35] compared China-III and China-IV heavy-duty diesel vehicles at an altitude of 3650 m. The experimental results showed that SCR can effectively affect NOx emissions and concluded that there is a strong correlation between the relative emission factors of O 2 and NOx and the average vehicle speed.…”
Section: Introductionmentioning
confidence: 99%